PENDAMPINGAN PENERAPAN STRATEGI DALAM MENGELOLA PERILAKU SISWA - Afriani, Afriani; Asmawiyah, Asmawiyah; Mukhtar, Afiah; Sulaiha Suwandi, Wisda; Islamiah, Nurhidayati; Basar, Nur Fatwa; Aisya, Nur (Arunika: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to improve the capacity of teachers in implementing effective student behavior management strategies at the Trisakti Makassar Education Foundation. The main problem faced by the school is the suboptimal understanding and skills of teachers in handling deviant student behavior, so a structured educational approach is needed. The activity methods include identifying needs, implementing interactive workshops and training, mentoring implementation in the classroom, and preparing a guide to student behavior management strategies. The results of the activity showed an 85% increase in teacher understanding of the concept of preventive, corrective, and promotive strategies based on values ​​and empathetic communication. In addition, there were positive changes in teacher-student interactions and the creation of a more conducive classroom environment. This activity is expected to be a mentoring model that can be replicated in other schools, as well as supporting the formation of student character in a sustainable manner.